Fabrication of a glucose oxidase/multiporous tin-oxide nanofiber film on Prussian blue–modified gold electrode for biosensing - A. K. M., Kafi; Alim, Samiul; Rajan, Jose; M. M., Yusoff (Elsevier, 2019)
Herein, we propose a new approach to fabricate an enzyme electrode based on immobilization of glucose oxidase (GOD) with multiporous nanofibers (MPNFs) of SnO2 on Prussian blue (PB) modified gold (Au) electrode with chitosan. MPNFs of SnO2 were synthesized by electrospinning method from the tin. Prussian blue was electrochemically deposited onto an Au electrode. GOD was then co-immobilized with the nanofibers on the surface of the PB modified gold electrode by using chitosan. The immobilized GOD/MPNFs onto the PB-Au presented faster, more stable and sensitive amperometric response to detecting glucose. Hydrogen peroxide (H2O2) produced via Glucose oxidation and glucose reaction was detected by Prussian blue. The linear response dependence on glucose concentration was observed in a range of 0.5–5 mM and a detection limit of 0.05 mM at 3 signal/noise ratio. Because of unique structural characteristics at the nanoscale level, multiporous nanofibers (MPNFs) of SnO2 is an ideal candidate for matrices in biosensing.